FINANCIAL ARCHITECTONICS AT THE LOCAL LEVEL: THROUGH DECENTRALIZATION TO A NEW PARADIGM - Mamonova V.V.; Olshanskyi O.V. (Pressing Problems of Public Administration, 2018)
In the article the components of  nancial architectonics at the local level are substantiated, the substantive essence of elements of such sectors as “Public Administration” and “Finance” are uncovered.